Pengaruh Motivasi Intrinsik, Motivasi Ekstrinsik dan Komitmen Pelayanan Tenaga Kesehatan Terhadap Kualitas Pelayanan BPJS Kesehatan - Much. Riyadus Solichin; Kabul Trifiyanto (P4M STIE Putra Bangsa, 2020)
The author of this paper aims to increase the delivery of health workers in private hospitals in serving patients using BPJS health. As for the background of this writing because now BPJS patients' views on health services are not good especially in private hospitals, marked by the issue of electronic media issues about public complaints that there are differences in health services provided by public hospitals compared to BPJS patients where parties public hospitals prioritize public patients more than patients participating in the health BPJS. This research is a quantitative study conducted through surveys and questionnaires. In this study involved 90 respondents in 9 private hospitals which are service providers in collaboration with BPJS in Kebumen Regency. For intrinsic motivation variable of 2,292 is greater than t table 1,198 with a significance value of 0.024 <0.05 so it can be concluded that the hypothesis is accepted. the t value for the extrinsic motivation variable is 0.029 smaller than t table 1.198 with a significance value of 0.977> 0.05 so it can be concluded that the hypothesis is rejected. t value for the commitment variable of 2.470 is greater than t table 1.198 with a significance value of 0.015 <0.05 so it can be concluded that the hypothesis is accepted. The results obtained are intrinsic motivation influencing the quality of labor services in private hospitals. So if the motivation of medical personnel services increases, the quality of services provided will increase. Extrinsic motivation does not affect the quality of labor services in private hospitals. So if the extrinsic motivation of medical personnel services increases / decreases, it cannot stimulate the quality of services provided. Commitment affects the quality of labor services in private hospitals. So if the commitment of medical personnel services increases, the quality of services provided increases. Intrinsic motivation, extrinsic motivation and commitment together affect the quality of labor services in private hospitals. So that the motivation of medical personnel services can stimulate the quality of services provided.